Porous, functionally gradient pyroelectric materials - Shaw, Christopher P.; Whatmore, Roger W.; Alcock, Jeffrey R. (Blackwell Publishing, 2007)
Properties of a new type of pyroelectric ceramic structure containing a layer of known porosity laminated between two dense layers, to form a functionally gradient material (FGM), are reported. The combination of theoretical models for pyroelectric, dielectric, and thermal properties gave a model for the pyroelectric voltage figure of merit (FV) in good agreement with experiment, which had shown a 20% improvement for an introduced central layer porosity of 27%. Preliminary pyroelectric responsivity measurements on FGM infrared detectors indicated an even better improvement. It is postulated that this is due to the porous layer acting as a thermal barrier in the structure.